Class-B CpG-ODN Formulated With a Nanostructure Induces Type I Interferons-Dependent and CD4+ T Cell-Independent CD8+ T-Cell Response Against Unconjugated Protein Antigen - Chiodetti, Ana L.; Sánchez Vallecillo, María F.; Dolina, Joseph S.; Crespo, María I.; Marin, Constanza; Schoenberger, Stephen P.; Allemandi, Daniel A.; Palma, Santiago D.; Pistoresi-Palencia, María C.; Morón, Gabriel; Maletto, Belkys A. (Frontiers in Immunology, 2018)
There is a need for new vaccine adjuvant strategies that offer both vigorous antibody and T-cell mediated protection to combat difficult intracellular pathogens and cancer. To this aim, we formulated class-B synthetic oligodeoxynucleotide containing unmethylated cytosine-guanine motifs (CpG-ODN) with a nanostructure (Coa-ASC16 or coagel) formed by self-assembly of 6-0-ascorbyl palmitate ester. Our previous results demonstrated that mice immunized with ovalbumin (OVA) and CpG-ODN formulated with Coa-ASC16 (OVA/CpG-ODN/Coa-ASC16) elicited strong antibodies (IgG1 and IgG2a) and Th1/Th17 cellular responses without toxic systemic effects. These responses were superior to those induced by a solution of OVA with CpG-ODN or OVA/CpG-ODN formulated with aluminum salts. In this study, we investigated the capacity of this adjuvant strategy (CpG-ODN/Coa-ASC16) to elicit CD8+ T-cell response and some of the underlying cellular and molecular mechanisms involved in adaptive response. We also analyzed whether this adjuvant strategy allows a switch from an immunization scheme of three-doses to one of single-dose. Our results demonstrated that vaccination with OVA/CpG-ODN/Coa-ASC16 elicited an antigen-specific long-lasting humoral response and importantly-high quality CD8+ T-cell immunity with a single-dose immunization. Moreover, Coa-ASC16 promoted co-uptake of OVA and CpG-ODN by dendritic cells. The CD8+ T-cell response induced by OVA/CpG-ODN/Coa-ASC16 was dependent of type I interferons and independent of CD4+ T-cells, and showed polyfunctionality and efficiency against an intracellular pathogen. Furthermore, the cellular and humoral responses elicited by the nanostructured formulation were IL-6-independent. This system provides a simple and inexpensive adjuvant strategy with great potential for future rationally designed vaccines.